دور التدريب في تحسين الخدمة العمومية - بوصبيع العايش, باسم. (جامعة الوادي University of Eloued, 2017)
لقد أصبح موضوع الخدمة العمومية يشكل اهتماما كبيرا لدى الدولة والمواطن، فالدولة تهدف من خلال إنشاء منظمات لتحقيق التزاماتها تجاه مواطنيها، والمواطن يصبو إلى تحقيق متطلباته. إلا أن المنظمات العمومية تبقى غير قادرة على تقديم خدمة ذات جودة، وهاته المنظمات ظلت تحتفظ بالأنماط التقليدية في التسيير لذا كان لزاما مواكبة العصرنة لتحسين خدماتها ليستفيد الجمهور. ويعتبر التدريب من أهم الأساليب الأكثر فعالية في هذا المجال بما يمتلكه من قدرة على الرفع من مستوى المردود البشري وزيادة كفاءته لذا تأتي هذه الدراسة لإبراز دور التدريب في تحسين الخدمة العمومية، وأهمية الدراسة تكمن في : 1 إبراز العلاقة بين أسلوب التدريب وموضوع تحسين الخدمة العمومية 2 جدية موضوع تحسين الخدمة في الدول العربية والجزائر، وخاصة في ظل التوجه نحو عصرنة الخدمة العمومية. The issue of public service has becomewith a greatconcern for the state and the citizens.The state aims to establish a lot of assossiationsto fulfillitscommitmentstowardsitscitizens.And the citizen aspire to achievehisrequirements. However, public organizationsremainunable to provide a highservice quality.Theseorganizations have maintainedtraditional pattern of governance.So, itisnecessarytokeeppace withmodernization to improveits service to benifit all people. The training isconsidered as one of the most effective methods in thisfieldwhich has the abilitytoraise the level of humanrole and increaseitsefficiency,sothisstudyis a wayto highlight the role of training in improving the public service. The importance of thisstudyis as follow: 1-To display the relationshipbetween the training method and the subjectof improving the public service. 2-Improving the service in the Arab countries and in Algeria as well, especiallyin the trend toward the modernization of ^public service.
سياسة عامة وإدارة محلية
Keywords: دور ،التدريب ،الخدمة ،تحسين; Role, training, service, improvement